ISU GENDER DALAM PEMBERITAAN ONLINE : ANALISIS PENGGUNAAN ISTILAH “SODOMI” PADA KORBAN KEKERASAN SEKSUAL LAKI-LAKI - Euzebia Valdiningsih Putri Ndia; An Nisa Dira Rasisa; Evan Nathaniel A (Universitas 17 Agustus 1945 Surabaya, 2026)
Online media plays a strategic role in shaping public perception of gender issues, particularly in reporting sexual violence. One issue that often arises is the use of the term “sodomy” in cases of sexual violence against male victims. This term is often used differently compared to the terms employed when the victims are female, such as “rape” or “sexual harassment.” This article aims to analyze gender bias in the use of the term “sodomy” in online media reporting and its impact on the construction of the meanings of victims and perpetrators. This study uses a qualitative approach with critical discourse analysis, framing analysis, and a gender studies perspective. The results of the analysis show that the use of the term “sodomy” is not neutral, but rather loaded with moral, historical, and stigmatizing connotations that can potentially undermine the recognition of men as victims of sexual violence. Therefore, the media need to use language that is more fair and gender-sensitive in order to promote a more equal public understanding of sexual violence issues.Keywords: Online Media, Sodomy, Gender Communication, Gender Inequality, Reporting